Upaya Meningkatkan Kemampuan Kepala Madrasah dan Guru dalam Menyusun Kurikulum KTSP melalui Bimbingan Teknis di MI Al Islam dan MI Al Ihsan Sleman - Sri Wahyuni (Jurnal Pendidikan Madrasah, 2019)
The research aims to know: 1) technical coaching in improving the ability of teachers to develop KTSP. 2) Increase the ability of teacher Madrasah in drafting KTSP document 1. The study used the research method of supervisory action with two cycles covering the planning, action, observation and reflection stages. Data is obtained through direct observation at the time the teacher compiled the curriculum and observation of the completed curriculum. The results showed as follows. Firstly, technical coaching was implemented for the teachers of the MI Al Islam curriculum Drafting team and the teachers of the MI Al Ihsan curriculum Drafting team separately. Secondly, the ability of the teachers of MI Al Islam in drafting the KTSP before technical coaching reaches a score of 41 or 51.25% admission criteria underprivileged, and MI Al Ihsan reached a score of 48 or 60% entered criteria quite capable. The ability after the technical coaching cycle I increased 10 points for the teachers of MI Al Islam reached a score of 51 or 63.75% up 12.5% of the entry criteria quite capable, the teachers of MI Al Ihsan up 14 points reached a score of 62 or 77.5% up 17.5% in the able criteria. In Cycle 2 The ability of MI Al Islam teachers in organizing the curriculum up 31 points or 38.75% from the initial state, enter the capable criteria (60-80). The ability of MI Al Ihsan's teachers to develop a curriculum up to 12 points reached an increase of 26 points or 33.5% from the initial state, entered the capable criteria (60-80).